Clinical Usefulness of the VS Classification System Using Magnifying Endoscopy with Blue Laser Imaging for Early Gastric Cancer - Yoshikazu Yoshifuku; Yoji Sanomura; Shiro Oka; Kazutaka Kuroki; Mio Kurihara; Takeshi Mizumoto; Yuji Urabe; Toru Hiyama; Shinji Tanaka; Kazuaki Chayama (Gastroenterology Research and Practice)
Background. Blue laser imaging (BLI) enables the acquisition of more information from tumors’ surfaces compared with white light imaging. Few reports confirm the validity of magnifying endoscopy (ME) with BLI (ME-BLI) for early gastric cancer (EGC). We aimed to assess the detailed endoscopic findings from EGCs using ME-BLI. Methods. We enrolled 386 consecutive patients with 417 EGCs that were diagnosed using ME-BLI and resected by endoscopic submucosal dissection. Using the VS classification system, three highly experienced endoscopists (HEEs) and three less experienced endoscopists (LEEs) evaluated the demarcation line (DL), microsurface pattern (MSP), and microvascular pattern (MVP) within the endoscopic images of EGCs obtained using ME-BLI, assigning high-confidence (HC) or low-confidence (LC) levels. We investigated the clinicopathological features associated with each confidence level. Results. The HEEs’ evaluations determined the presence of DL in 99%, irregular MSP in 96%, and irregular MVP in 96%, and the LEEs’ evaluations determined the presence of DL in 98%, irregular MSP in 95%, and irregular MVP in 95% of the EGCs. When DL was present, HC levels in the Helicobacter pylori- (H. pylori-) eradicated group and noneradicated group were evident in 65% and 89%, a difference that was significant (p<0.001). Conclusions. In the diagnosis of EGC with ME-BLI, the VS classification system with ME-NBI can be applied, but identifying the DL after H. pylori was difficult.